Komunitas Mangrove di Area Konservasi Mangrove PT Petrokimia Gresik: Ekowisata Mangrove Kali Lamong Gresik - Cundaningsih, Nurvita; Shidqi, Muhammad Daffa; Fadilah, Kabul; Prasetya, Azhim Agni; Amelia, Verona (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The mangrove communities and their utilization for ecotourism are situated along the Kali Lamong riverbanks, specifically in Sukorejo Village, Kebomas District, Gresik Regency. In the context of area management, it is crucial to understand the current state of the mangrove community through an analysis of the biodiversity index and important value index. The method used in this study is the line plot transect method. Data were analyzed using the Shannon-Wiener Diversity Index to determine the value of the Biodiversity Index and also calculate the density, frequency and dominance to determine the Important Value Index (IVI). The results of the data analysis indicated that there were 10 mangrove species found in the sampling area. The highest Biodiversity Index was in the category of mangrove saplings, namely 1,83; trees of 1,67; and seedlings of 1,33. The highest Importance Value Index is in the tree category mangrove with an IVI value of 98,66, namely the Avicennia marina mangrove. Meanwhile, the mangrove IVI in the sapling category with the highest value was Rhizophora mucronata, which was 82,75; and IVI of the highest category of seedlings also belongs to the Avicennia marina mangrove, which is 54,25.